Measuring Financial Performance Over Profitability Ratio Analysis - Laelisneni; Era Purike; Okta Selvia Br Ginting; Nur Azizah; Priatna Kesumah (SEAN Institute, 2022)
Financial reports are documents or written records that convey a company's business activities and financial performance. This study aims to determine the company's financial performance as measured using profitability ratios. The purpose of the profitability ratio is to measure a company's ability to earn profits (profits) each year. The data analysis method used is quantitative, focusing only on numbers with a descriptive approach. The data collection technique used in this study is in the form of a report via the company's official website and then takes the company's financial statements. The data analysis technique used by the author is a descriptive analysis that explains financial performance with tables, graphs, and pictures. The results of this study indicate that the company's financial performance measured through Return On Assets is below the standard ratio set, meaning that ROA is not good. Financial performance is measured through Return On Equity which is below the standard ratio set, meaning that ROE is not good. Financial performance measured through Net Profit Margin is below the standard ratio set, which means that the NPM needs to be better formed.